Perda de eficiência em redução de atrito em escoamentos com altos números de Reynolds em tubos com pressão de entrada fixa - Sandoval, Gustavo Alonso Barrientos (2015)
The addition of small parts per million of high molecular weight polymer in turbulent flow produces a significant decrease in the friction factor. This phenomenon known as drag reduction () has become of great interest for the industrial and scientist community because of the great advantages in several engineering areas. However, the drag reduction efficiency is not constant, due to interaction between the additive with turbulent eddies that causes the breakdown of the molecular structure of the polymer chain. Researches have reported that this degradation depends on factors as: Reynolds number, temperature, additive type, its concentration and molecular weight. The phenomenon is not completely understood and many aspects of the problem remain unclear. Important issues are related to the development of turbulent structures after the additive injection and the breaking or aggregation in the polymer molecules. In the present work is investigated the drag reduction efficiency in dilute aqueous solutions for three different polymers: Poly(ethylene oxide) (PEO), Polyacrylamide (PAM) and Xanthan Gum (XG). The first two are known as flexible molecules while the last one is considered rigid. An experimental apparatus made up of pipes disposed in series configuration is used for the realization of the experiments, in which the material of the main section of the test is of stainless steel with polished treatment. The drag reduction effects produced by the variation of the concentration and the molecular weight are analyzed. The main results are displayed in terms of absolute drag reduction. Besides that, is shown and quantified the flow rate increase and the decrease of the pressure drop in the pipe, despite of tests being conducted at a fixed inlet pressure in the apparatus. Aiming to observe the degradation, the absolute drag reduction results are reorganized and displayed in terms of a relative drag reduction, ′. Posteriorly, these same ′ data are adjusted by means of a decaying function that is based on the equation proposed by Pereira and Soares (2012) for a rotating cylindrical device. Finally, there are shown some promising results that are obtained by mixing the polymers studied in this work.